Youth-oriented active labour market policies: explaining policy effort in the nordic and the baltic states - Tosun, Jale; Unt, Marge; Wadensjö, Eskil (Social policy and administration, 2017)
The starting point of this study is the seemingly striking similarity in the number of youth-oriented labour market policies adopted by the Nordic and the Baltic EU member states in 2013-14 despite markedly different welfare regimes. The similarities remain when concentrating on active labour market policies (ALMPs) and extending the observation period to 2007-15, but the application of a more refined coding scheme suggests that there are also notable cross-country differences. Estonia, Finland and Sweden are found to exhibit a relatively similar approach to youth-oriented ALMPs, while Denmark, Latvia and Lithuania are more distinct cases. The similarities in the policy effort can be explained by similar problem pressure, EU-guided policy learning and the provision of EU funding. Lastly, the policy approaches of the Nordic states indicate a path-dependency. Thus, while the youth-oriented policy effort may appear to be quite similar, important differences remain.